2018
DOI: 10.1097/wad.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

The p.R47H Variant of TREM2 Gene is Associated With Late-onset Alzheimer Disease in Colombian Population

Abstract: Objective: We evaluated the association of several single-nucleotide polymorphisms in the triggering receptor expressed on myeloid cells 2 (TREM2) gene in a Colombian sample of late-onset Alzheimer disease (LOAD). Methods: The p.Q33* (rs104894002), p.R47H (rs75932628), p.R62H (rs143332484), and p.D87N (rs142232675) variants of TREM2 gene were directly genotyped using KASPar technology in 358 cases and 329 healthy controls. Sanger sequencing was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The authors concluded that TREM2 R47H could be an important LOAD risk factor, but more studies are necessary to corroborate the relationship described. 48 In Colombia, a recent study about LOAD genetics has also been performed. 49 It evaluated the association of 14 single-nucleotide polymorphisms in genes that have been connected to LOAD and confirmed this relationship through a genome-wide association study.…”
Section: Other Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that TREM2 R47H could be an important LOAD risk factor, but more studies are necessary to corroborate the relationship described. 48 In Colombia, a recent study about LOAD genetics has also been performed. 49 It evaluated the association of 14 single-nucleotide polymorphisms in genes that have been connected to LOAD and confirmed this relationship through a genome-wide association study.…”
Section: Other Mutationsmentioning
confidence: 99%
“…In 2018, Arboleda-Bustos et al 48 studied the association between several TREM2 polymorphisms and LOAD. They found a relationship with the TREM2 arginine to histidine substitution at amino acid 47 ( R47H ) in a sample of 358 AD cases and 329 controls; specifically, this variant was identified in six LOAD probands: five (5/558 or 1.4%) heterozygous and one (1/358 or 0.28%) homozygous.…”
Section: Colombiamentioning
confidence: 99%
See 1 more Smart Citation
“…Additional rare variants, including p.Arg62His (R62H, rs143332484), p.Asp87Asn (D87N, rs142232675) and p.His157Tyr (H157Y, rs2234255), have also been detected in AD subjects and indicated to increase the susceptibility to AD (11,12). Furthermore, certain TREM2 mutations, such as p.Gln33stop, p.Tyr38Cys and Thr66Met, have been identified only in patients with AD but not in normal controls, and appear to be causative (13), However, due to the low frequency of these variants, studies with a small sample size may not have adequate power to identify the genetic associations (14)(15)(16). The results of association studies from different regions and ethnicities are not always consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the extracellular domain of TREM2 confer an elevated risk of developing late-onset AD. A risk allele (R47H) of TREM2 had an effect similar to ApoE4 (odds ratio 2.90-5.05) in a Colombian population 23 . TREM2 is a receptor expressed in macrophages including microglia in the brain.…”
Section: Microgliamentioning
confidence: 90%